Determinantes da mortalidade neonatal em Fortaleza-Ceará : um estudo de caso-controle - Nascimento, Renata Mota do (2011)
Neonatal mortality is influenced by a complex interplay of socioeconomic, biological and social assistance. In the last two decades the mortality in the perinatal and neonatal periods not suffered significant declines, due to persistent high levels of mortality factors related to pregnancy and childbirth. Currently, neonatal mortality accounts for 60% to 70% of infant mortality in all regions of Brazil. Studies designed to investigate the determinants of neonatal mortality have been widely developed in Brazil, however, case-control studies using primary data have not been developed in the city of Fortaleza-Ce in recent years. The study aimed to determine factors associated with neonatal deaths in Fortaleza in 2009. Were the specific objectives of this series to describe the socioeconomic and demographic characteristics of mothers and newborns in cases (neonatal deaths) and controls (newborn survivors), to identify the features related to prenatal care, childbirth and newborn and neonatal deaths of infants surviving and determine predictors of neonatal mortality using hierarchical modeling. Methodological terms, this was a study of case-control, with 132 cases of neonatal deaths and 264 controls obtained among survivals of the neonatal period. For cases were considered children born alive and died before 28 days of life and how those controls remained alive during this period, born in Fortaleza-Ce and children of mothers living in the city. The information was obtained through home interviews using a structured questionnaire. Variables were grouped into four groups according to hierarchical conceptual model: Block 1-socioeconomic and demographic characteristics; bloco2-maternal characteristics, reproductive history, maternal morbidity, maternal behavior, social support and exposure to violence; 3-block handling characteristics of the pre prenatal and childbirth; block 4-sex and health of the newborn. The model of hierarchical logistic regression analysis identified factors associated with neonatal death: Block 1 - maternal race with a protective effect against brown and black race (OR: 0.23, 95% CI 0.09 to 0.56), block 3 - between the time spent commuting from home to hospital less than 30 minutes (OR: 3.12, 95% CI 1.34 to 7.25), less than 1 hour or greater than or equal to 10 hours between admission and delivery (OR: 2.43, 95% CI 1.24 to 4.76) and inadequate prenatal care (OR: 2.03, 95% CI 1.03 to 3.99) Block 4 - low weight birth (OR: 14.75, 95% CI 5.26 to 41.35), prematurity (OR: 3.41, 95% CI 1.29 to 8.98) and male (OR: 2.09, CI 95% 1.09 to 4.03). This series has revealed aspects of the determination of neonatal deaths related to the quality of prenatal care offered to pregnant women, supply of hospital beds, indicating the pilgrimage of pregnant women seeking maternity, as well as aspects related to direct assistance to labor, translated determining the time over 10 hours elapsed between admission and delivery in pregnant women.